The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1186/cc6829
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal dopamine attenuates pulmonary edema and improves survival after ventilator-induced lung injury in rats

Abstract: Intoduction Clearance of alveolar oedema depends on active transport of sodium across the alveolar-epithelial barrier. β-Adrenergic agonists increase clearance of pulmonary oedema, but it has not been established whether β-agonist stimulation achieves sufficient oedema clearance to improve survival in animals. The objective of this study was to determine whether the increased pulmonary oedema clearance produced by intratracheal dopamine improves the survival of rats after mechanical ventilation with high tidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…These results support the general finding that age increases the incidence and severity of edema (5)(33). They also demonstrate our experimental model’s ability to induce ventilator-associated pulmonary edema with HVT mechanical ventilation and subsequently attenuate it through conservative fluid administration alone.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results support the general finding that age increases the incidence and severity of edema (5)(33). They also demonstrate our experimental model’s ability to induce ventilator-associated pulmonary edema with HVT mechanical ventilation and subsequently attenuate it through conservative fluid administration alone.…”
Section: Discussionsupporting
confidence: 90%
“…Pulmonary edema is a hallmark of VILI and the severity and susceptibility to pulmonary edema increases with age (25)(5)(21)(41). Some of the driving forces behind development and progression of pulmonary edema both in general and in VILI are increases in pulmonary intravascular pressure, decreased epithelial barrier integrity/increased permeability, and increased local and systemic inflammatory cytokine presence.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not differentiate between interstitial and alveolar edema [1]. The wet-to-dry ratios in our study were similar to those in Sprague-Dawley rats [35,38,48], but higher than those reported in Wistar-Kyoto rats [49]. The increase in wet-to-dry ratio was evident as early as 30 minutes, but remained the same for up to 60 minutes.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with the idea of β -agonists as potential therapeutic tools, β -adrenergic agonist treatment improved fluid clearance and edema resolution in experimental models of ALI/ARDS [6871]. The activation of transepithelial Na + transport and alveolar fluid clearance by β -adrenergic agonists was also shown to reduce extravascular lung water in patients who were part of the so-called BALTI trial ( beta-agonist lung injury trial, BALTI ), a clinical trial that addressed the possibility of β -agonist treatment in ALI/ARDS [72].…”
Section: Na+ Channels As Molecular Targets For the Treatment Of Pumentioning
confidence: 82%